(untitled) (Nordic Journal of African Studies, 1996)
• P. Kishindo Fanner Turn Over on Settlement Schemes: The Experience of Limphasa Irrigated Rice Scheme, Northern Malawi • R. O. Lasisi Liquor Traffic in Africa under the League of Nations 1919-1945: French Togo as an Example • P. K. Agbedor The Structure and Language of Ewe Libation Prayer • M. Woube Environmental Deterioration in Sub-Saharan Africa (SSA): The Challenge of Sustainable Development • E. Bertoncini-Ziibkova A Stylistic Analysis of Mohamed Suleiman’s Short Story: Uhuru wa Siku Moja • A. A. Amidu Kiswahili, a Continental Language: How Possible Is It? (Part II) continued from NJAS 4:2 • R. E. S. Tanner Some Reflections on a foreigner’s use of Swahili • L. Njinya-Mujinya lnforrnation Banks in Rural Africa: A Missing Building Block • K. A. Acheampong The Democratization Process in South Africa: Implications for Human Rights Promotion and Protection in the Southern African Sub-Region